Filling the gaps: Original chronologies of silver fir (Abies alba Mill.) and European beech (Fagus sylvatica L.) living trees in the French PyreneesDataverse - Mélanie Saulnier; Vincent Labbas; Roberta D’Andréa; Sylvain Burri; Laurent Larrieu; Sylvain Morvan; Nicolas Martin; Caroline Scotti-Saintagne; Frédéric Jean; Nicolas Poirier; Vanessa Py-Saragaglia (Data in Brief)
Between 2016 and 2024, as part of several research projects on forest history in the mountain belt of the central French Pyrenees, we cored 360 living trees at breast height, including 309 silver fir (Abies alba Mill. 1768) and 51 European beech (Fagus sylvatica L. 1753), using an increment drill. In addition, 64 cross-sections of beech stems were harvested with a chainsaw during a forest cut by the forest manager. The trees are located in 14 stands (13 fir-dominated forests with some beech, 1 beech-dominated forest, in 3 stands we sampled both species) spread over the French Central Pyrenees and subject to different levels of harvesting pressure: regularly harvested, harvested 30-40 years ago, not harvested for a long time (>100 years). In each stand, we established three to five circular plots of 1 ha each. Depending on the main objective of the research projects, trees were selected from the largest, dominant or co-dominant individuals according to a pre-established protocol, as for the BENDYS project [1] (full description in Py-Saragaglia et al., 2020), or to represent the full range of diameter at breast height (DBH) available in the 1 ha circular plots. All samples were processed using standard dendrochronological techniques at the GEODE laboratory in Toulouse (PANGEME analysis platform). Tree-ring measurements were made with a resolution of 0.001 mm using either a LINTAB sliding table connected to TsapWin software (RINNTECH, Heidelberg, Germany) or CooRecorder [2] software applied to a high-resolution scan of the samples. All samples were cross-dated using CDendro [2] software. The robustness of the chronologies was assessed using reference curves available for both species in the Pyrenees for beech and in southern France for fir.The present dataset provides two reference chronologies for fir and beech in this part of the Pyrenees and 17 master stand chronologies, 13 from fir and 4 from beech. The reference chronologies were constructed from 324 of the 424 individual ring series sampled, 253 from fir (309 sampled) and 71 from beech (115 sampled). All reference chronologies are suitable for dendroarchaeological studies (dating, dendroprovenance, reconstruction of ancient practices, etc.), dendroecological studies (resilience of species, effect of management on growth, etc.) and dendroclimatological studies (climate reconstruction, climate sensitivity of the two species, etc.).